Membros: v. 3, n. 2 (2005) - ., .. (RENOTE, 2005)
Julio Alberto Nitzke - SEAD/UFRGSMarcus Vinícius de Azevedo Basso - Instituto de Matemática/UFRGS Rosa Maria Vicari - Instituto de Informática/UFRGS Liane Margarida Rockenbach Tarouco - CINTED/UFRGS Mára Lúcia Fernandes Carneiro - UERGS Ricardo Azambuja Silveira - UFPel Patrícia Alejandra Behar - Faculdade de Educação/UFRGS Magda Bercht - Instituto de Informática/UFRGS Margarete Axt - PGIE/UFRGS Marie Jane Soares Carvalho - PPGEDU/UFRGS Gilse Antoninha Morgental Falkembach - UNIFRA Coordenação : Liane Margarida Rockenbach Tarouco - CINTED/UFRGS